Rancang Bangun Masjid Raya Universitas Samudera Aceh Berbasis Perencanaan Fungsional dan Strategis - Sani, Andi Asrul; Wijayanti, Hendry; Alim, Zaenul; Sobri, Muh. Rofif (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2021)
The aim of planning the construction of the Grand Mosque of Universitas Samudera Aceh (UNSAM) was to help Universitas Samudra in Langsa city so that the construction of a new mosque in the campus environment has a large capacity with self-managed construction. The methods used for the study were literature design, site survey, interior spatial analysis, design planning. The findings and implications of a well design and planning is that it is hoped the mosque becomes the pride of the campus residents in particular and the people of Langsa city in general. It is also hoped to be able to support religious activities and worship for all academicians of Universitas Samudera.Â